The effects of oxygen addition on microstructure and mechanical properties of Ti-Mo alloys for biomedical application - Kobayashi, Sengo; Okano, Satoshi (Frontiers in Bioengineering and Biotechnology, 2024)
The effective use of oxygen as an alloying element in Ti alloys is attractive due to the reduction of production cost and the increase in strength and hardness of the alloy. Although the oxygen addition in a Ti alloy increases strength and hardness, it may induce brittleness. An appropriate combination of alloying elements and thermomechanical treatment must be clarified for the use of oxygen as an alloying element. Ti-(0, 1.0, 2.0, 3.0)Mo-(0, 1.5, 3.0)O alloys were developed, and their microstructure and mechanical properties were examined. Ti-1Mo-3O alloy exhibited fine grains of α+β two phases having the tensile strength of 1297 MPa with 15.5 % for total strain at fracture. The Ti-1Mo-3O alloy has 1.5 times the tensile strength and the same total strain as the Ti-6Al-4V ELI alloy. Ti-(1.0, 2.0, 3.0)Mo-1.5O alloys also have excellent mechanical properties, with tensile strength of about 1050-1150 MPa and a total strain of about 20-25 %. In order to develop a high strength and moderate ductility Ti-Mo alloy using oxygen as an alloying element, the microstructure should have fine grains of α+β two phases with proper volume fraction of α and β phases and specific molybdenum concentration in β phase.